Reflections on Matters of War and Peace - Jamshed Ayaz Khan, Major Gen. (Islamabad, Pakistan PanGraphics, 2003)
Collection of articles chiefly published in Pakistani dailies from 1991 to 2003.
Include Colour Illustration
Keywords: Pakistan -- Politics and government